Artikel PEMBELAJARAN MATEMATIKA BERMUATAN JENGAH DENGAN SETTING INVESTIGATION UNTUK PEMAHAMAN DAN KEYAKINAN DIRI - Ayu Puskita Dewi; I Made Ardana; Gde Sueken (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2019)
This study aimed to determine whether the cooperative learning model type Investigation (GI) is loaded jengah concept has a positive effect on conceptual understanding of mathematics and self efficacy student’s. This research was using experiment with post-test only control group design which consist of 543 students as the population in twelve classes. Sampling in this research using cluster random sampling technique. VIII.K as an experiment class and VIII.I as the control class were determined randomly with the draw system. The research was conducted 8 times meeting. Data collection techniques with test and non-test. The data in this research was collected by the essay test of conceptual understanding of mathematics and keyakinan diri questionnaire. Both tests were given at the end of the study. Data were analyzed using the Manova one-way test. The result of the research shows the ability of conceptual understanding of mathematics and keyakinan diri of students who follow cooperative type learning model GI is loaded jengah concept with media of learning Geogebra better than the ability of students who follow conventional learning.